A cellulose composite membrane based on hydrogen-bonded organic frameworks and a preparation method and application thereof
Patent Information
- Application Number
- CN202611080666.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]针对现有技术的HOF材料无法规模化制膜的不足,本发明的目的在于提供一种基于氢键有机框架的纤维素复合膜及其制备方法和应用,提供一种卷对卷连续两步浸渍工艺,实现了在常温常压下规模化制备超大尺寸HOF-21@BC复合膜,实现对PFAS的高效去除
(1)本发明开发了氢键有机框架材料的卷对卷连续化制备新工艺,能够稳定生产出大幅宽、超长尺寸的复合膜卷材,突破了传统釜式反应仅能获得厘米级样品的尺寸局限。整个制备过程在常温常压下完成,无需配置高温高压设备,大幅降低了设备投资;同时选用成本低廉的原料体系,相比于金属有机框架或共价有机框架改性膜,显著节约了原料成本和能源消耗,具备优异的工业化放大前景。
Smart Images

Figure CN122999003A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of environmental functional membrane materials technology, and in particular to a cellulose composite membrane based on a hydrogen-bonded organic framework, its preparation method, and its application. Background Technology
[0002] Per- and polyfluoroalkyl substances (PFAS) are a class of synthetic fluorine-containing organic compounds. The carbon-fluorine bonds in their molecules have extremely high bond energy, giving these compounds exceptional chemical stability, thermal stability, and environmental durability, hence they are called "permanent chemicals." Perfluorooctanoic acid (PFOA) is widely used in the processing of electroplating, fire-fighting foams, textiles, semiconductors, and military industries, and is discharged into surrounding water bodies and groundwater through wastewater. PFOA can bioaccumulate at each level of the food chain, and long-term exposure can cause liver and kidney damage, reproductive toxicity, and even induce cancer in humans. Given its serious health risks, in 2023, the U.S. Environmental Protection Agency lowered the recommended safe level for PFOA in drinking water to 4 ng / L. However, the concentration of PFOA in actual industrial contaminated sites, groundwater around airports, and surface lakes often exceeds the standard by hundreds to tens of thousands of times, highlighting the urgent need to develop high-performance and engineerable water treatment technologies.
[0003] Currently, adsorption is widely recognized as an effective method for removing PFOA from water. However, mainstream adsorbents (such as activated carbon, ion exchange resins, and emerging metal / covalent organic frameworks (MOF / COF)) are mostly in powder form, which presents inherent drawbacks in practical applications, including difficulties in recovery, easy clogging of equipment, and difficulty in integration into continuous flow systems. These limitations severely restrict their deployment in large-scale water treatment scenarios. On the other hand, existing commercial membrane technologies also have significant bottlenecks: while reverse osmosis membranes have high rejection rates, they consume enormous amounts of energy; nanofiltration membranes have relatively low energy consumption, but they cannot guarantee deep purification of PFOA (rejection rates are typically below 90%). The aforementioned trade-off between rejection rate and flux, as well as the difficulties in large-scale preparation of membrane materials, have become the core pain points restricting the development of PFOA pollution control technologies.
[0004] Hydrogen-bonded organic frameworks (HOFs) are a class of porous crystalline materials formed through self-assembly via intermolecular hydrogen bonds. They possess advantages such as tunable pore structure, mild synthesis conditions, and reversible regeneration of the hydrogen bond network, theoretically making them an ideal platform for PFOA adsorption. However, current research is still limited to the laboratory preparation of powdered HOF crystals. There are no reports on continuous, large-scale HOF-based functional membranes and their roll-to-roll mass production processes, and even fewer engineering examples of their use for deep PFAS removal.
[0005] Cellulose (BC), as a renewable and biodegradable natural polymer material, possesses a three-dimensional nanofiber network, high hydrophilicity, and excellent mechanical flexibility, making it an ideal membrane substrate. However, pure cellulose membranes lack affinity sites for PFOA and have extremely low PFOA retention capacity, making them unsuitable for direct use in PFAS treatment.
[0006] Therefore, how to maintain the excellent substrate properties of cellulose membranes while using HOF materials to endow them with efficient and stable PFAS capture capabilities and achieve large-scale membrane fabrication is a technical problem that urgently needs to be solved. Summary of the Invention
[0007] To address the limitation of existing HOF materials in large-scale membrane fabrication, the present invention aims to provide a cellulose composite membrane based on a hydrogen-bonded organic framework, its preparation method, and its application. It also provides a roll-to-roll continuous two-step impregnation process, enabling the large-scale preparation of ultra-large-size HOF-21@BC composite membranes at room temperature and pressure, achieving efficient removal of PFAS.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: A cellulose composite membrane based on a hydrogen-bonded organic framework includes a cellulose membrane and a hydrogen-bonded organic framework grown in situ on the cellulose membrane, wherein the structural formula of the hydrogen-bonded organic framework is as follows: .
[0009] The present invention also provides a method for preparing the cellulose composite membrane described above, comprising the following steps: S1. Immerse the cellulose membrane in a Cu(NO3)2·3H2O aqueous solution impregnation tank to obtain Cu. 2+ @BC composite membrane; S2, Cu 2+ @BC composite membranes are continuously immersed in an acetonitrile-water mixed solution containing adenine and (NH4)2SiF6 to react and obtain HOF-21@BC composite membranes; S3. The HOF-21@BC composite membrane after exiting the tank is continuously sprayed with acetonitrile and deionized water, dried with low-temperature hot air, and then continuously wound up to obtain the cellulose composite membrane.
[0010] Specifically, the BC membrane is first uniformly passed through an immersion tank containing an aqueous solution of Cu(NO3)2·3H2O, where it is immersed to react. The abundant hydroxyl groups on the BC surface react with the Cu... 2+ Coordination occurs, yielding Cu 2+ @BC composite film; then Cu 2+ The BC composite membrane is continuously immersed in an acetonitrile-water mixed solution containing adenine and (NH4)2SiF6 at room temperature. 2+@Cu surface coordination of BC composite film 2+ HOF-21 was generated in situ by self-assembly with adenine and (NH4)2SiF6 to obtain HOF-21@BC composite membrane. Finally, the HOF-21@BC composite membrane after exiting the tank was continuously sprayed with acetonitrile and deionized water to remove free HOF-21 and ligands on the surface. It was then dried with low-temperature hot air and continuously wound up to obtain a continuous large-size functional membrane.
[0011] The preparation method of this invention is suitable for preparing small-sized laboratory samples and can also be adapted to roll-to-roll continuous processes to achieve mass production of large-sized industrial membranes. It can adapt to different production scales simply by adjusting the length of the impregnation tank and controlling the speed of the cellulose membrane, without changing the core reaction parameters, demonstrating strong process adaptability. Compared to the limitations of traditional batch synthesis, which can only prepare small-sized membrane samples, this process overcomes the size limitations of HOF-based functional membranes, allowing them to be cut to any size according to actual application needs, meeting the assembly requirements of membrane modules of different specifications.
[0012] Based on the above technical solutions, preferably, in step S1, the concentration of the Cu(NO3)2·3H2O aqueous solution is 50-250 mmol / L.
[0013] More preferably, the concentration of the Cu(NO3)2·3H2O aqueous solution is 250 mmol / L.
[0014] Based on the above technical solutions, preferably, in step S1, the reaction temperature is 20-30℃ and the time is 1-8h.
[0015] More preferably, in step S1, the reaction time is 1 hour.
[0016] Based on the above technical solutions, preferably, in step S2, the concentration of adenine in the acetonitrile-water mixed solution is 10-100 mmol / L.
[0017] More preferably, the concentration of adenine in the acetonitrile-water mixed solution is 50 mmol / L.
[0018] Based on the above technical solution, preferably, in step S2, the molar ratio of adenine to (NH4)2SiF6 is 1:0.5-4.
[0019] More preferably, in step S2, the molar ratio of adenine to (NH4)2SiF6 is 1:0.5.
[0020] Based on the above technical solutions, preferably, in step S2, the volume ratio of acetonitrile to water in the acetonitrile-water mixed solution is 1:1-2.
[0021] More preferably, in step S2, the volume ratio of acetonitrile to water in the acetonitrile-water mixed solution is 1:1.
[0022] Based on the above technical solutions, preferably, in step S2, the reaction temperature is 20-30℃ and the time is 6-18h.
[0023] More preferably, in step S2, the reaction time is 12 hours.
[0024] The present invention also provides an application of the cellulose composite membrane in PFAS separation.
[0025] Based on the above technical solutions, a preferred embodiment includes the following steps: assembling the cellulose composite membrane into a membrane module, and continuously passing PFOA-containing wastewater through the cellulose composite membrane under constant pressure.
[0026] Specifically, the cellulose composite membrane is cut to the required size, assembled into a membrane module, and PFOA-containing wastewater is continuously passed through the cellulose composite membrane under constant pressure. The filtrate is then measured using UPLC-ESI-MS, and the measurement results are analyzed and calculated.
[0027] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention develops a novel roll-to-roll continuous preparation process for hydrogen-bonded organic framework materials, which can stably produce composite film rolls with wide and ultra-long dimensions, breaking through the size limitation of traditional batch reactions that can only obtain centimeter-sized samples. The entire preparation process is completed at room temperature and pressure, without the need for high-temperature and high-pressure equipment, which greatly reduces equipment investment; at the same time, it uses a low-cost raw material system, which significantly saves raw material costs and energy consumption compared with metal-organic frameworks or covalent organic framework modified films, and has excellent prospects for industrial scale-up.
[0028] (2) This invention utilizes the inherent multi-level pore structure of the hydrogen-bonded organic framework to construct a highly efficient water molecule transport channel within the composite membrane. At the same time, by leveraging the multiple synergistic capture mechanisms such as Lewis acid-base interactions, hydrogen bonding interactions, specific interactions between carbon and fluorine bonds, and dipole interactions within the framework, it achieves ultra-high retention of perfluorooctanoic acid and exhibits excellent water flux performance. This effectively solves the long-standing technical problem of mutual constraint between retention rate and flux in traditional nanofiltration and reverse osmosis membranes, and can meet the treatment requirements for deep purification of drinking water.
[0029] (3) The cellulose composite membrane based on a hydrogen-bonded organic framework prepared in this invention exhibits excellent stability and sustainability in practical applications. Even under complex water quality conditions such as high salinity and the coexistence of multiple ions, its removal performance for perfluorooctanoic acid remains highly stable. After use, the membrane material can be efficiently regenerated by simple rinsing at room temperature with inexpensive organic solvents, making the operation process simple and easy. In addition, using bacterial cellulose as the substrate material gives the composite membrane good biodegradability, allowing for green and harmless treatment after disposal, which aligns with the development concepts of circular economy and green environmental protection. Attached Figure Description
[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0031] Figure 1 This is a schematic diagram of the preparation method of the cellulose composite membrane based on the hydrogen-bonded organic framework of the present invention; Figure 2 This is a physical illustration of the cellulose composite membrane based on a hydrogen-bonded organic framework according to the present invention. Figure 3 The PXRD pattern of the cellulose composite membrane based on a hydrogen-bonded organic framework prepared in Example 5; Figure 4 The infrared spectrum of the cellulose composite membrane based on a hydrogen-bonded organic framework prepared in Example 5; Figure 5 The image shows a scanning electron microscope (SEM) image of the cellulose composite membrane based on a hydrogen-bonded organic framework prepared in Example 5. Figure 6 This is a comparison chart showing the PFOA removal rejection rate and water flux performance of Comparative Example 1 and Example 5 in pure water and Example 5 in salt solution. Detailed Implementation
[0032] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0033] It should be noted that, unless otherwise specified, all chemical reagents involved in this invention are purchased through commercial channels or synthesized from raw materials purchased through commercial channels.
[0034] In all embodiments and comparative examples of this invention, the BC membrane has a width of 0.6 m and a length of 10 m.
[0035] Example 1 This embodiment provides a method for preparing a cellulose composite membrane based on a hydrogen-bonded organic framework, comprising the following steps: First, the BC membrane was uniformly passed through an immersion bath containing a 50 mmol / L Cu(NO3)2·3H2O aqueous solution for 8 hours, and then washed multiple times with purified water to obtain Cu. 2+ @BC composite membrane. Subsequently, Cu... 2+ The BC composite membrane was immersed in an acetonitrile-water mixed solution containing 100 mmol / L adenine and 200 mmol / L ammonium hexafluorosilicate (acetonitrile to water volume ratio 1:1, adenine to ammonium hexafluorosilicate molar ratio 1:2) and reacted at room temperature (25℃) for 6 hours. After sequentially spraying with pure acetonitrile for 1 min and deionized water for 2 min, the membrane was dried in a 50℃ hot air drying channel and continuously wound up by a winding roller to obtain the cellulose composite membrane.
[0036] Example 2 This embodiment provides a method for preparing a cellulose composite membrane based on a hydrogen-bonded organic framework, comprising the following steps: First, the BC membrane was uniformly passed through an immersion tank containing a 100 mmol / L Cu(NO3)2·3H2O aqueous solution for 4 hours, and then washed multiple times with pure water to obtain Cu. 2+ @BC composite membrane. Subsequently, Cu... 2+ The BC composite membrane was immersed in an acetonitrile-water mixed solution containing 80 mmol / L adenine and 200 mmol / L ammonium hexafluorosilicate (acetonitrile to water volume ratio 1:1, adenine to ammonium hexafluorosilicate molar ratio 1:2.5) and reacted at room temperature (25℃) for 10 h. After sequentially spraying with pure acetonitrile for 1 min and deionized water for 2 min, the membrane was dried in a 50℃ hot air drying channel and continuously wound up by a winding roller to obtain the cellulose composite membrane.
[0037] Example 3 This embodiment provides a method for preparing a cellulose composite membrane based on a hydrogen-bonded organic framework, comprising the following steps: First, the BC membrane was uniformly passed through an immersion bath containing a 150 mmol / L Cu(NO3)2·3H2O aqueous solution for 2 hours, and then washed multiple times with purified water to obtain Cu. 2+ @BC composite membrane. Subsequently, Cu... 2+The BC composite membrane was immersed in an acetonitrile-water mixed solution containing 50 mmol / L adenine and 150 mmol / L ammonium hexafluorosilicate (acetonitrile to water volume ratio 1:1, adenine to ammonium hexafluorosilicate molar ratio 1:3) and reacted at room temperature (25℃) for 14 h. After being sprayed sequentially with pure acetonitrile for 1 min and deionized water for 2 min, the membrane was dried in a 50℃ hot air drying channel and continuously wound up by a winding roller to obtain the cellulose composite membrane.
[0038] Example 4 This embodiment provides a method for preparing a cellulose composite membrane based on a hydrogen-bonded organic framework, comprising the following steps: First, the BC membrane was uniformly passed through an immersion bath containing a 200 mmol / L Cu(NO3)2·3H2O aqueous solution for 1 hour, and then washed multiple times with purified water to obtain Cu. 2+ @BC composite membrane. Subsequently, Cu... 2+ The BC composite membrane was immersed in an acetonitrile-water mixed solution containing 10 mmol / L adenine and 40 mmol / L ammonium hexafluorosilicate (acetonitrile to water volume ratio 1:1, adenine to ammonium hexafluorosilicate molar ratio 1:4) and reacted at room temperature (25℃) for 18 h. After being sprayed sequentially with pure acetonitrile for 1 min and deionized water for 2 min, the membrane was dried in a 50℃ hot air drying channel and continuously wound up by a winding roller to obtain the cellulose composite membrane.
[0039] Example 5 This embodiment provides a method for preparing a cellulose composite membrane based on a hydrogen-bonded organic framework, comprising the following steps: First, the BC membrane was uniformly passed through an immersion bath containing a 250 mmol / L Cu(NO3)2·3H2O aqueous solution for 1 hour, and then washed multiple times with purified water to obtain Cu. 2+ @BC composite membrane. Subsequently, Cu... 2+ The BC composite membrane was immersed in an acetonitrile-water mixed solution containing 50 mmol / L adenine and 25 mmol / L ammonium hexafluorosilicate (acetonitrile to water volume ratio 1:1, adenine to ammonium hexafluorosilicate molar ratio 1:0.5) and reacted at room temperature (25℃) for 12 h. After being sprayed sequentially with pure acetonitrile for 1 min and deionized water for 2 min, the membrane was dried in a 50℃ hot air drying channel and continuously wound up by a winding roller to obtain the cellulose composite membrane.
[0040] Comparative Example 1 This embodiment provides a cellulose membrane for use as a blank control. The blank control processing method includes the following steps: First, the BC membrane was passed through a deionized water immersion tank at a constant speed for 1 hour, and then washed with pure water multiple times. After that, it was immersed in an acetonitrile-water mixed solution (volume ratio 1:1) immersion tank and left at room temperature (25℃) for 12 hours. Then, it was sprayed with pure acetonitrile for 1 minute and deionized water for 2 minutes in sequence. Finally, the membrane was dried in a 50℃ hot air drying channel and continuously wound up by a winding roller to obtain a cellulose membrane for blank control.
[0041] (1) PFOA removal test in pure water The cellulose composite membranes prepared in Examples 1-5, the cellulose membrane obtained from Comparative Example 1 (used as a blank control), and the commercial nanofiltration membrane from Comparative Example 2 were applied to remove PFOA, as follows: After being cut to 4 x 4 cm size, the membrane was assembled into a module. PFOA was added to 500 mL of pure water under a constant pressure of 0.6 MPa to achieve an initial concentration of 50,000 ng / L. -1 The solution was then continuously passed through a membrane module, and the filtrate was measured using UPLC-ESI-MS. The measurement results were then analyzed and calculated.
[0042] (2) PFOA removal test in salt solution The cellulose composite membranes prepared in Examples 1-5, the cellulose membrane obtained from Comparative Example 1 (used as a blank control), and the commercial nanofiltration membrane from Comparative Example 2 were applied to remove PFOA, as follows: After being cut to a size of 4 x 4 cm, the membrane module was assembled. PFOA was added to 500 mL of a salt solution (a mixed salt solution of magnesium chloride, calcium chloride, zinc chloride, potassium chloride, and sodium chloride, each with a concentration of 0.05 mmol / L) under a constant pressure of 0.6 MPa, to achieve an initial concentration of 50,000 ng / L. -1 The solution was then continuously passed through a membrane module, and the filtrate was measured using UPLC-ESI-MS. The measurement results were then analyzed and calculated.
[0043] The test results are shown in Table 1 below.
[0044] Table 1 Performance Test Results As can be seen from Table 1 above, the cellulose composite membrane based on hydrogen-bonded organic framework prepared in this invention exhibits significantly better PFOA retention performance and water flux than the blank cellulose membrane without a hydrogen-bonded organic framework. Example 5 shows the best performance, with a PFOA retention rate of 99.9% and a water flux of 86.3 m³ / s. -2 h -1 bar -1 It achieves both high rejection rate and high throughput, demonstrating excellent potential for PFAS separation applications.
[0045] Furthermore, the cellulose composite membrane of Example 5 maintained a PFOA rejection rate of 99.0% in high-salinity water, with only a very slight decrease, while the water flux remained at 81.1 m³. -2 h -1 bar -1 It still exhibits excellent retention and permeability, proving that the composite membrane can still stably perform PFOA removal under high-salt and complex water quality conditions, meeting the application requirements of actual wastewater treatment.
[0046] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A cellulose composite membrane based on a hydrogen-bonded organic framework, characterized in that, It includes a cellulose membrane and a hydrogen-bonded organic framework grown in situ on the cellulose membrane, the structural formula of which is as follows: 。 2. A method for preparing a cellulose composite membrane as described in claim 1, characterized in that, Includes the following steps: S1. Immerse the cellulose membrane in a Cu(NO3)2·3H2O aqueous solution impregnation tank to obtain Cu. 2+ @BC composite membrane; S2, Cu 2+ @BC composite membranes are continuously immersed in an acetonitrile-water mixed solution containing adenine and (NH4)2SiF6 to react and obtain HOF-21@BC composite membranes; S3. The HOF-21@BC composite membrane after exiting the tank is continuously sprayed with acetonitrile and deionized water, dried with low-temperature hot air, and then continuously wound up to obtain the cellulose composite membrane.
3. The method for preparing the cellulose composite membrane as described in claim 2, characterized in that, In step S1, the concentration of the Cu(NO3)2·3H2O aqueous solution is 50-250 mmol / L.
4. The method for preparing the cellulose composite membrane as described in claim 2, characterized in that, In step S1, the reaction temperature is 20-30℃ and the time is 1-8h.
5. The method for preparing the cellulose composite membrane as described in claim 2, characterized in that, In step S2, the concentration of adenine in the acetonitrile-water mixed solution is 10-100 mmol / L.
6. The method for preparing the cellulose composite membrane as described in claim 5, characterized in that, In step S2, the molar ratio of adenine to (NH4)2SiF6 is 1:0.5-4.
7. The method for preparing the cellulose composite membrane as described in claim 2, characterized in that, In step S2, the volume ratio of acetonitrile to water in the acetonitrile-water mixed solution is 1:1-2.
8. The method for preparing the cellulose composite membrane as described in claim 2, characterized in that, In step S2, the reaction temperature is 20-30℃ and the time is 6-18h.
9. The application of the cellulose composite membrane as described in claim 1 in PFAS separation.
10. The application as described in claim 9, characterized in that, Includes the following steps: The cellulose composite membrane is assembled into a membrane module, and PFOA-containing wastewater is continuously passed through the cellulose composite membrane under constant pressure.
